ASPECTOS DO DIAGRAMA DIALETAL DOS PRONOMES PESSOAIS, EM PARTICULAR DO NEO-JÔNIO DE HERÓDOTO - Arns, Osvaldo (Revista Letras, 1964)
ASPECTOS DO DIAGRAMA DIALETAL DOS PRONOMES PESSOAIS, EM PARTICULAR DO NEO-JÔNIO DE HERÓDOTO